PENGARUH BUDAYA ORGANISASI, PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. TIRTA INVESTAMA (Dc BALI) - Putu Pradiva Putra Salain; I Nyoman Resa Adhika; I Gede Rihayana (Universitas Mahendradatta, 2022)
This study aims to determine the effect of organizational culture, training and workdiscipline on employee performance at PT. Tirta Investama (Dc Bali). The dominantphenomenon in this study is employee perception regarding new habits in working during theCOVID-19 pandemic and several other phenomena related to employee performance, namelytraining that has not been maximized and the disciplined attitude of employees at work. Thefocus of the object in this study is organizational culture, training and work discipline onemployee performance with the population used is all employees of PT. Tirta Investama (DcBali). Determination of the sample in this study using the Slovin approach, where the sampleused 83 employees. The technique used is multiple linear regression analysis. The test resultsshow that organizational culture has a positive and significant effect on the performance ofemployees of PT. Tirta Investama (Dc Bali), Training has a positive and significant effect onthe performance of employees of PT. Tirta Investama (Dc Bali) and work discipline have apositive and significant effect on employee performance at PT. Tirta Investama (Dc Bali).